Digital Marketing Strategy and Customer Rating: Impact on Purchase Decisions at Sinar Mandiri - Dewi, Myla Sunar; Hayati, Nur (Widya Cipta: Jurnal Sekretari dan Manajemen, 2026)
The rapid growth of digital technology has transformed marketing practices, forcing businesses to adopt digital platforms in order to remain competitive and influence consumer behavior. In this environment, digital marketing strategies and customer rating play an increasingly important role in shaping purchasing decisions, especially for retail businesses operating in highly competitive markets. However, empirical evidence regarding the effectiveness of these factors in the context of local retail is still limited. This study uses an explanatory quantitative approach to analyze the impact of digital marketing strategies and customer evaluation on purchasing decisions at Sinar Mandiri. Data was collected from customers who had made purchases and been exposed to the company’s digital marketing activities through social media, online marketplaces, and other digital platforms using a five-point Likert scale questionnaire. The data was analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results of the study indicate that both digital marketing strategies and customer rating have a positive and significant influence on purchasing decisions, with digital marketing strategies showing a stronger influence. These findings suggest that effective digital marketing serves as a major stimulus in shaping consumer expectations, while customer evaluations reinforce trust and perceived quality in the decision-making process. These results have practical implications for local retail businesses in developing more targeted digital marketing strategies and managing customer feedback to improve purchasing decisions.